Strategies for Partnership Toward Better Local Service Quality - Said, Abas; Yaakub, Ahmad Nizar (Universiti Malaysia Sarawak, UNIMAS, 2014)
Tourism is rapidly becoming a major industry in Malaysia in tenus of its contribution to the economy. Tourism contribution to the GDP' s increased rapidly over the past 15 years before the East Asian Economic crisis in 1997. Following the financial crisis, tourism is identified as one of the priority sectors to regain economic growth. As such sustaining tourism growth is important to complement growth of the overall economy and most important to expedite Malaysia' s economic recovery. The government of Malaysian's commitment to tourism development is demonstrated in the 7th Malaysia Plan (1996-2000). According to Economic Report for 1998/99, the federal government has spent about RM 500 million on tourism in the 7th Malaysia Plan. In the 8th Malaysia Plan (2001-2005), tourism sector is expected to continue to gain financial support from the government.